Corporate Postretirement Benefit Plans and Real Investment - Bartram, Söhnke M. (Management Science, 2017)
This paper shows that the real investment by nonfinancial firms is systematically related to the size of their defined-benefit plan. In particular, these plans allow research and development (R&D)-intensive firms to retain and borrow from their employees, which is attractive since they have high adjustment costs, require a stable cash flow, have less collateral, have assets that are harder to value, and have high asymmetric information and agency costs. By contrast, capital expenditures benefit from credit multiplier effects with regard to regular debt, which substitutes for postretirement obligations. As a result, firms with defined-benefit plans have 12% more R&D and 5% less capital expenditure compared with otherwise similar firms, and they vary contributions as a function of cash flow and real investment. The role of postretirement plans is attenuated in countries with available alternative funding sources. The results are robust to controlling for other dimensions of financial policy—cash holdings, debt maturity, dividends, preferred stock, convertible debt, and leverage—that also affect real investment. This paper was accepted by Gustavo Manso, finance.